2021
DOI: 10.1002/pol.20210399
|View full text |Cite
|
Sign up to set email alerts
|

The chemical effect of furfuryl amide on the enhanced performance of the diphenolic acid derived bio‐polybenzoxazine resin

Abstract: As a renewable chemical, diphenolic acid (DPA) has attracted immense interest in bio-based polymer science. However, its application for polybenzoxazines is limited due to decarboxylation, that is, the release of CO 2 during the curing reaction of benzoxazine. In this study, the amidation strategy of converting DPA to diphenolic amides (DPAM) was demonstrated to solve this problem while simultaneously improving the thermal properties of polybenzoxazine. DPA was amidated by separately using four amines (hexamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 57 publications
4
32
0
Order By: Relevance
“…It was observed that the storage modulus ( E ′) for PTCDPF gradually decreased from 1650 MPa at 30 °C to 940 MPa at 250 °C, indicating that the polymer retained good mechanical properties upon raising temperature. The T g value of PTCDPF was as high as 322 °C, which exceeded those of most known amide‐containing polybenzoxazines 37,38 . This result confirmed that the thermomechanical property of polymer could be improved significantly by introducing diketopiperazine units into the molecular backbone.…”
Section: Resultssupporting
confidence: 59%
See 4 more Smart Citations
“…It was observed that the storage modulus ( E ′) for PTCDPF gradually decreased from 1650 MPa at 30 °C to 940 MPa at 250 °C, indicating that the polymer retained good mechanical properties upon raising temperature. The T g value of PTCDPF was as high as 322 °C, which exceeded those of most known amide‐containing polybenzoxazines 37,38 . This result confirmed that the thermomechanical property of polymer could be improved significantly by introducing diketopiperazine units into the molecular backbone.…”
Section: Resultssupporting
confidence: 59%
“…The estimated cross‐linking density value of PTCDPF was 23 mol dm −3 , which was higher than those of the reported polybenzoxazines 38,41,42 …”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations